2011
DOI: 10.1353/jhr.2011.0011
|View full text |Cite
|
Sign up to set email alerts
|

Childcare, Eldercare, and Labor Force Participation of Married Women in Urban China, 1982-2000

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…This fl exibility wanted to work, and allowed fi rms to choose who to hire and fi re. This fl exibility also gave rise to the possibility of unemployment (Meng 2000;, and Zhao also gave rise to the possibility of unemployment (Meng 2000;Cai, Park, and Zhao 2009;Maurer-Fazio, Connelly, Chen, andTan 2010). 2009;Maurer-Fazio, Connelly, Chen, and Tan 2010).…”
Section: Urban Labor Market Reform Employment and Unemploymentmentioning
confidence: 99%
See 2 more Smart Citations
“…This fl exibility wanted to work, and allowed fi rms to choose who to hire and fi re. This fl exibility also gave rise to the possibility of unemployment (Meng 2000;, and Zhao also gave rise to the possibility of unemployment (Meng 2000;Cai, Park, and Zhao 2009;Maurer-Fazio, Connelly, Chen, andTan 2010). 2009;Maurer-Fazio, Connelly, Chen, and Tan 2010).…”
Section: Urban Labor Market Reform Employment and Unemploymentmentioning
confidence: 99%
“…This change in employment among older workers probably resulted from workers who lost jobs employment among older workers probably resulted from workers who lost jobs because of economic restructuring and then became discouraged and left the labor because of economic restructuring and then became discouraged and left the labor force (Appleton, Knight, Song, and Xia 2002;Giles, Park, and Cai 2006;Maurerforce (Appleton, Knight, Song, and Xia 2002;Giles, Park, and Cai 2006;MaurerFazio, Connelly, Chen, and Tang 2010). Fazio, Connelly, Chen, and Tang 2010).…”
Section: Urban Labor Market Reform Employment and Unemploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-reform, state and employer support for care provision in the form of subsidized childcare or paid maternity leave has declined (Zhan, 2002). In rural areas, the closure of collective farms has forced women to engage with informal or precarious forms of employment (Maurer-Fazio et al, 2011), or else migrate to urban areas and export zones, leaving behind elderly parents and young children (Zhou et al, 2014). The erosion of social services and the privatization of care services have coincided with a re-emergence of traditional patriarchal values and norms involving notions of filial piety within a patrilineal family system.…”
Section: Contextual Changes and Their Implications For Care Policies mentioning
confidence: 99%
“…There is an extensive and mixed literature on tradeoffs between caring for seniors and female labor force participation, some finding evidence of a tradeoff, and others finding that caring for an aging parent does not reduce the amount of time women spend in the labor force, since co-residing parents can provide care for young children, freeing up time for formal work (Johnson and Lo Sasso 2006;Latif 2006;Maurer-Fazio et al 2011;Sasaki 2002;Wakabayashi and Donato 2005;Wolf and Soldo 1994). Qualitative research in Egypt has suggested that with rising levels of female employment, there is increasing tension between women's labor force participation and their ability to care for aging in-laws (Sinunu, Yount, and El Afify 2008).…”
Section: Women's Labor and Leisurementioning
confidence: 99%